Effectiveness of Aquaflor (50% Florfenicol) Administered in Feed to Control Mortality Associated with Streptococcus iniae in Tilapia at a Commercial Tilapia Production Facility. (3rd September 2014) - Gaikowski, Mark P.; Schleis, Susan M.; Leis, Eric; Lasee, Becky A.; Endris, Richard G.
Abstract: The efficacy of Aquaflor (florfenicol; FFC) to control mortality caused by Streptococcus iniae in tilapia was evaluated under field conditions. The trial was initiated following presumptive diagnosis of S. iniae infection in a mixed group of fingerling (mean, 4.5 g) Nile Tilapia Oreochromis niloticus and a hybrid of Nile Tilapia×Blue Tilapia O. aureus . Diagnoses included mortality in source tank; examination of clinical signs and presence or absence of gram‐positive cocci in brain, and collection of samples for microbiological review and disease confirmation of 60 moribund fish. Following presumptive diagnosis, tilapia (83/tank) were randomly transferred to each of 20 test tanks receiving the same water as the source tank (test tank water was not reused). Tilapia were offered either nonmedicated control feed or FFC‐medicated feed (FFC at 15 mg/kg body weight/d; 10 tanks per regimen) for 10 consecutive days followed by a 14‐d observation period during which only the nonmedicated control feed was offered. Streptococcus iniae was presumptively identified during pretreatment necropsy and confirmed by polymerase chain reaction assay; S. iniae was confirmed in samples taken during the dosing period but was not detected during the postdosing period. The FFC disk diffusion zone of inhibition ranged from 29 to 32 mm, while the minimum inhibitory concentration of FFC ranged from 2 to 4 μg/mL for the S. iniae isolates collected. Survival of tilapia assigned to the FFC‐dose group was significantly greater at 14 d posttreatment than that of the nonmedicated controls. The odds of tilapia assigned to the FFC‐dose group surviving to the end of the postdosing period were 1.34 times the odds of survival of tilapia assigned to the nonmedicated control group. There were no clinically apparent adverse effects associated with the administration of FFC‐medicated feed in this study.